Hereditary benign intraepithelial dyskeratosis: Is this the first African case? - Loubab Omahsan (Our Dermatology Online, 2018)
Inherited benign intraepithelial dyskeratosis (IBID) is a rare genodermatosis, affecting both the oral and conjunctival mucosa. We report a new case of a 10-year-old girl with clinico-histological manifestations of IBID and melkersson rosenthal syndrome. IBID manifests itself by whitish, painless, spongy papules or plaques of varying sizes sitting mainly at the side edges of the tongue. The Melkerson Rosenthal syndrome is a rare disease, to be evoked in the framework of pathologies of the big lips. The association of these two pathologies is unusual.